Educação de jovens e adultos: análise da política e da prática de formação de educadores no Programa Brasil Alfabetizado - Sepúlveda, Francisca Gorete Bezerra (2009)
The current research has the objective to analyze the public policies of formation (initial and continuing) of educators for young people and adults, in the Brazilian education scenario. Upon the numerous questions included in several researches on this theme, our curiosity has been focused on the investigation of advances and difficulties on the formation of educators for young people and adults, from 2000 to 2006. To illustrate this matter, we analyzed the Programa Brasil Alfabetizado, (from 2003 to 2006) and the MOVA/Guarulhos, intending on identifying possible advances on the proposals and practices of new educators formation. To comprehend the political and pedagogical relations in this process, to compose our theoretical referential, we based our studies on Beisiegel, Paiva, Haddad, Di Pierro and Freire. This research has taken a qualitative approach. The methodological procedures included bibliography research and analysis of documents. For collecting the field data, semi-structured interviews were made to educators of young people and adults of MOVA/Brasil Alfabetizado in Guarulhos and analysis of literacy and educators formation policies documents of Programa Brasil Alfabetizado. The qualitative analysis of the testimonies, interviews and documents revealed, among other aspects, that the educators formation policy has been registering advances in the pedagogical proposals and the methodological orientations. It was also concluded that progress has been made in the socio-educational actions targeted to learners, in the articulation of educational policies integrated to social policies of the Federal Government. Our analysis has revealed that the principles which orientate the public policies of young people and adults literacy are based on political-pedagogical references of Paulo Freire s philosophy. Thus, it has been concluded that the literacy conception has changed from a limited view of reading, writing and counting, to a wider comprehension, understanding literacy as a political-educational process of insertion of man in the world, aiming transformation. Despite the improvements, it has been noticed that the formation of young people and adults educators still characterizes itself as a fragile process by the fact that those educators remain in a situation of volunteers. It is added to that the severe statement that most of them do not have the teachers formation for being so. It could also be identified a reduction in the time of capacitating practices of those educators as regards to the amount of hours. The time that has been dedicated to capacitating is 30 hours for initial formation and 2 hours for continuing formation, what is, doubtless, absolutely insufficient. For the policies of teacher qualification for young people and adults to ensure greater effectiveness in the process of literacy, given the indications and guidelines for research, it is important to be made serious investment of the government in the training of educators, including, here, the opportunity to that these can be trained in universities